Glyphosate, AMPA and glufosinate in soils and earthworms in a French arable landscape. (August 2022) - Pelosi, C.; Bertrand, C.; Bretagnolle, V.; Coeurdassier, M.; Delhomme, O.; Deschamps, M.; Gaba, S.; Millet, M.; Nélieu, S.; Fritsch, C.
Abstract: Although Glyphosate-based herbicides are often marketed as environmentally friendly and easily biodegradable, its bioavailability and risks to wildlife raise significant concerns. Among non-target organisms, earthworms which live in close contact with the soil can be directly exposed to pesticides and harmed. We investigated soil contamination and the exposure of earthworms to glyphosate, its metabolite AMPA, and glufosinate in an arable landscape in France, both in treated (i.e. temporary grasslands and cereal fields under conventional farming), and nontreated habitats (i.e. hedgerows, permanent grasslands and cereal fields under organic farming) (n = 120 sampling sites in total). Glyphosate, AMPA and glufosinate were detected in 88%, 58% and 35% of the soil samples, and in 74%, 38% and 12% of the earthworm samples, respectively. For both glyphosate and AMPA, concentrations in soils were at least 10 times lower than predicted environmental concentrations. However, the maximum glyphosate soil concentration measured (i.e., 0.598 mg kg −1 ) was only 2 to 3 times lower than the concentrations revealed to affect earthworms (survival and avoidance) in the literature. These compounds were found both in conventional and organic farming fields, thus supporting a recent study, and for the first time they were detected in hedgerows and grasslands. However, glyphosate and AMPA were more frequently detected in soils from cereal fields and hedgerows than in grasslands, and median concentrations measured in soils from cereal fields were significantly higher than in the two other habitats. Bioaccumulation of glyphosate and AMPA in earthworms was higher than expected according to the properties of the molecules. Our findings raised issues about the high occurrence of glyphosate and AMPA in soils from cropped and more natural areas in arable landscapes. They also highlight the potential for transfer of these molecules in terrestrial food webs as earthworms are prey for numerous animals. Graphical abstract: Image 1 Highlights: Glyphosate, AMPA, and glufosinate were measured in 120 soils and earthworms. Glyphosate was detected in 88% and 74% of the soil and earthworm samples, respectively. Soil concentrations of glyphosate were at least 10 times lower than PECs. Mean soil concentrations were not influenced by pesticide use or cropping systems. Bioaccumulation of glyphosate and AMPA was higher than expected by molecule properties.